A Topographic Atlas of the Human Brainstem in the Ponto-Mesencephalic Junction Plane - Coulombe, Vincent; Saikali, Stephan; Goetz, Laurent; Takech, Mohamad A.; Philippe, Éric; Parent, André; Parent, Martin (Frontiers in Neuroanatomy, 2021)
The human brainstem harbors neuronal aggregates that ensure the maintenance of several vital functions. It also acts as a major relay structure for the neuronal information that travels between the cerebral cortex, the cerebellum and the spinal cord. As such, this relatively small portion of the human brain houses a multitude of ascending and descending fibers that course among numerous nuclei whose exact boundaries are still uncertain. Such a large number of nuclei and fiber tracts confined to a relatively small and compact brain region imposes upon the brainstem a highly complex cytoarchitectonic organization that still needs to be deciphered. The present work provides a topographic atlas of the human brainstem composed of 45 anatomical plates, each containing a pair of adjacent sections stained with Cresyl Violet and Luxol Fast Blue to help delineating brainstem nuclei and fiber tracts, respectively. The plates, which cover the entire midbrain, pons and medulla oblongata, are composed of equally-spaced sections referenced and aligned parallel to the ponto-mesencephalic junction rather than the fastigium or the obex. This topographic landmark is particularly suitable for neurosurgical interventions aiming at specific nuclei of the mesencephalic tegmentum. In complement, we provide 8 anatomical plates containing adjacent sections stained for choline acetyltransferase and Luxol Fast Blue, taken through the midbrain and the pons. This open access atlas of the human brainstem is intended to assist neuroanatomists, neurosurgeons and neuropathologists in their work.